Indicators in Improving Corporate Compliance on Human Rights : Indicators in Human Rights Governance and the EU Directive on Non-Financial Information - Kahiluoto, Joanna (fi=Turun yliopisto|en=University of Turku|, 2018)
The increasing use of indicators in global governance facilitates transforming complex phenomenon into simple and easily comparable numbers. There are, however, certain implications in employing indicators into international law. This study analyzes the corporate responsibility on human rights and the use of indicators in protecting human rights. The focus of the study is on the recognized problematics of the use of indicators and particularly on how such problematics have been addressed in the European Union Directive 2014/95/EU on disclosure of non-financial information. As an identified issue of the increasing reporting, the corporate motives for social reporting are evaluated in the light of their impact on the quality and reliability of the reported data. Problems of the indicators focus on the relation between increased use of indicators and the concrete improvement of human rights, and particularly on the risk of creating superficial compliance. In addition, the compatibility of the use of indicators as tools of policy making and the risk of losing the humane side of human rights are discussed.